PERAN PENURUNAN BERAT BADAN TERHADAP KADAR PLASMINOGEN ACTIVATOR-1 PADA OBESITAS ABDOMINAL - Budhiarta, A.A.Gd. (journal of internal medicine; Vol. 7, No. 3 September 2006, 2012)
Analytical cross-sectional study involving 77 subjects (male 31, female 46) with abdominal obesity (Ab- Ob) and 27 subjects non obese (male 20; female 7), age between 30-60 years were conducted and continued with randomized pre-post test control group study involving 66 subjects (male 25, female 41) with Ab-Ob recruited from the analytical cross-sectional study. Using random permuted block 30 subjects ( male 12; female 18) were treated with hypocaloric diet and regular physical exercise for 12 weeks and 36 subjects (male 13; female 23) as controls. Compare with non obese subjects there were higher levels of active PAI-1, insulin and HOMA-IR in subjects with Ab-Ob (p<0.001 ; p = 0.001 and p < 0.001 respectively). There were significant correlation between fasting insulin level and HOMA-IR with active PAI-1 ( r = 0.488, p <0.001 and r = 0. 543, p <0.001 respectively). Among treated group decreased in body weight 5.9 kg or 7.4% followed by decreased in WC ( p <0.001), insulin (p = 0.005), and active PAI-1 (p <0.001). Among treated group decreased in WC ( p<0.001), insulin (p = 0.001), and active PAI-1 ( p = 0.003) were higher than control group. There were positive correlation between decreased body weight ( r = 0.297; p <0,001), decreased decreased FBS ( r = 0.307 ; p = 0.012), decreased insulin (r = 0.360 ; p = 0.003), with decreased active PAI-1. To test the independence of associations between decreased in active PAI-1 and decreased body weight, fasting blood sugar and insulin levels during program, a multivariate linear regression analysis was performed. Only decreased in body weight and decreased fasting blood sugar significantly and independently associated with decreased in active PAI-1 and accounted for 23.4% of the variance of decreased in active PAI-1. Decreased body weight accounted for 17.1% and decreased fasting blood sugar accounted for 6.3% of decreased in active PAI-1.
Keywords: abdominal obesity, insulin, insulin resistance, plasminogen activator inhibitor-1.